Assessment of Spring Distribution across Pakistan: Implications for Water Security - Akbar, Ghani; Iqbal, Muhammad Bilal (The Nucleus, 2025)
Springs play a vital role in Pakistan’s water security, particularly in remote regions where they serve as a lifeline for agriculture, livestock, and domestic needs. However, increased pressure on spring resources from climate change, population growth, deforestation, and land degradation has significantly reduced their availability. Springs have been largely overlooked in both research and policy formulation in Pakistan. This study assesses the distribution and status of springs across Pakistan’s main provinces and regions. Focusing on the springs data from the 2023 Survey of Pakistan, along with population data from the 2023 census and climatic data from the nearest stations of Pakistan Meteorological Department, this study maps the spatial distribution of springs and examines the influence of environmental parameters, such as rainfall, temperature, elevation, and slope on their existence. The findings highlight that 81% of the nation’s springs are concentrated in Khyber Pakhtunkhwa (KP) and Baluchistan provinces, with substantial regional dependency on these resources. The Hindu Kush Himalaya (HKH) region of Pakistan hosts around 5051 springs (28%) in Pakistan. Approximately 114 million people live in 108 spring districts with an average of around 25000 persons per spring, while the average spring density is around three springs per ten thousand hectares. Through province-level mapping, this study underscores the urgent need for sustainable policies to conserve springs and improve water security. This study emphasized the need for sustainable water management policies and their urgent field implementation that prioritize spring conservation and adaptation to climate change impacts.